Occurrence of incidents at a surgical center: a documentary study - Willyara Rodrigues Bezerra; Ana Lúcia Queiroz Bezerra; Thatianny Tanferri de Brito Paranaguá; Milton Junio Cândido Bernardes; Cristiane Chagas Teixeira (Universidade Federal de Goias, 2015)
The objective of the study was to estimate the prevalence of incidents occurred during surgeries at a surgical center and to analyze the types and causes of occurrences. A cross-sectional retrospective study, having as data source 300 records of patients submitted to surgery procedures during July and December of 2013, at a teaching hospital from the Central-Western Region of Brazil. A total of 26 incidents were found and the estimated prevalence was 8.7%. Incidents related to the suspension of surgeries, gloves perforations, and accidents with the patient by technical failures in the procedure and, technical failures on the service management were attributed to team distraction, prescription failure, lack of knowledge, work overload, and failure of service organization. The study found the incident systemic and multi-factorial characteristic and brought up indicators for the need of improvements on the management process of materials and human resources.